The Effect of Periodontitis on Expression of Interleukin-21: A Systematic Review - Archana Mootha; Sankari Malaiappan; N. D. Jayakumar; Sheeja S. Varghese; Julie Toby Thomas (International Journal of Inflammation)
Purpose. Inflammation and tissue breakdown are led by an array of inflammatory destructive mediators associated with initiation and progression of inflammatory diseases like periodontitis. Current evidence shows that these inflammatory mediators have a definitive role in the pathogenesis of various systemic diseases with an inflammatory component. Interleukin-21 (IL-21) has been associated with systemic diseases like rheumatoid arthritis and Crohn’s disease that follow a chronic inflammatory cascade. Similarly recent studies have associated Interleukin-21 levels with periodontitis. This systematic review was aimed to assess the levels of IL-21 in subjects with periodontitis. Methods. A complete literature search was done in PubMed, Medline, Science Direct, and Cochrane databases and Google Scholar based on the inclusion/exclusion criteria. Six relevant articles were procured. Full text was read individually by two reviewers and data extraction was done based on STROBE statement. Results. After data extraction five observational and one interventional study were obtained. All the studies showed an increased expression of IL-21 in periodontitis and the interventional study showed reduction in IL-21 levels after nonsurgical periodontal therapy (NSP). Conclusion. Interleukin-21 levels are higher in periodontitis than controls. With this limited evidence further longitudinal studies are required to consider this as a definitive inflammatory marker.